Framework problem solving based augmented reality media to empower scientific explanation skill - Lilya Vany Wisma Widiana; Baskoro Adi Prayitno; Bowo Sugiharto (JPBI (Jurnal Pendidikan Biologi Indonesia), 2024)
Development of scientific explanation abilities in students is an important aspect in science education. However, traditional learning methods such as textbooks and PowerPoint presentations are often less effective in improving skills due to lack of student interactivity and involvement in the learning process. This study aimed to analyze the effectiveness of using augmented reality media based on problem-solving frameworks to empower scientific explanation. The research design was used a Nonrandomized Control Group, Pretest-Posttest Design. The study used a quasi-experimental method with a factorial design of 2 x 2. The research sample was 72 students, one of senior high school in Indonesia. The sample was divided into two groups: the control group using two-dimensional learning media based on books, PowerPoints, and videos. The treatment group used augmented reality learning media based on problem-solving frameworks. The material used in the study is the human circulation system in biology subjects. The instrument used to obtain scientific explanation data is an essay test developed from scientific explanation indicators adapted from McKneill et al. Data analysis using ANCOVA (p=0.05%) with pre-test values as covariates. The results showed that augmented reality media based on problem-solving frameworks could empower and more significantly improve the ability of scientific explanation, this is evidenced by the average value of scientific explanation skills in the experimental class is higher than the control class.